Expression of annexin-A1 in blood and tissue leukocytes of leprosy patients - Ribeiro, Afonso Bezerra (Rev Soc Bras Med Trop, 2020)
INTRODUCTION: In leprosy, immune system mediators that regulate the infectious process act in a complex manner and can lead to several clinical outcomes. To understand the behavior of these mediators we quantified the expression of annexin-A1 (ANXA1) in the peripheral blood and plasma as well as tissue leukocytes in all clinical forms of leprosy and compared with healthy controls. METHODS: Seventy healthy controls and 70 patients with leprosy, tuberculoid (TT) (n = 13), borderline tuberculoid (BT) (n = 15), borderline borderline (BB) (n = 13), borderline lepromatous (BL) (n = 15), and lepromatous leprosy (LL) (n = 14), were selected. Phenotyping of the lymphocyte cells and the intracellular expression of ANXA1 in leukocytes was performed by immunofluorescence. Plasma protein levels were determined by enzyme-linked immunosorbent assay. RESULTS: Histiocytes and CD4(+) and CD8(+) T cells in the skin of BL and LL patients had higher ANXA1 expression. ANXA1 expression was also high in circulating polymorphonuclear, monocytes, and CD4(+) and CD8(+) T cells in the blood of LL patients compared to those of TT, BT, BB, and BL patients, and these levels were similar to those in healthy controls. Plasma ANXA1 levels indicate an increase in paracrine release in patients with LL. CONCLUSIONS: The data indicate that ANXA1 expression is enhanced in the leukocytes and plasma of patients with LL, and may contribute to the inhibition of leukocyte action, leading to inadequate functioning of the immune system and thus contributing to the spread of M. leprae infection.